Comparative genomics of the fungal pathogens Candida dubliniensis and Candida albicans - Jackson, Andrew P.; Gamble, John A.; Yeomans, Tim; Moran, Gary P.; Saunders, David; Harris, David; Aslett, Martin; Barrell, Jamie F.; Butler, Geraldine; Citiulo, Francesco; Coleman, David C.; de Groot, Piet W.J.; et al. (Genome Research, 2009)
Candida dubliniensis is the closest known relative of Candida albicans, the most pathogenic yeast species in humans. However, despite both species sharing many phenotypic characteristics, including the ability to form true hyphae, C. dubliniensis is a significantly less virulent and less versatile pathogen. Therefore, to identify C. albicans-specific genes that may be responsible for an increased capacity to cause disease, we have sequenced the C. dubliniensis genome and compared it with the known C. albicans genome sequence. Although the two genome sequences are highly similar and synteny is conserved throughout, 168 species-specific genes are identified, including some encoding known hyphal-specific virulence factors, such as the aspartyl proteinases Sap4 and Sap5 and the proposed invasin Als3. Among the 115 pseudogenes confirmed in C. dubliniensis are orthologs of several filamentous growth regulator (FGR) genes that also have suspected roles in pathogenesis. However, the principal differences in genomic repertoire concern expansion of the TLO gene family of putative transcription factors and the IFA family of putative transmembrane proteins in C. albicans, which represent novel candidate virulence-associated factors. The results suggest that the recent evolutionary histories of C. albicans and C. dubliniensis are quite different. While gene families instrumental in pathogenesis have been elaborated in C. albicans, C. dubliniensis has lost genomic capacity and key pathogenic functions. This could explain why C. albicans is a more potent pathogen in humans than C. dubliniensis.